Effectiveness of Central Bank Swap Lines in Alleviating the Mispricing of FX Swaps at the Start of the COVID-19 Pandemic - Patty Duijm; Kai Schellekens (Applied Finance Letters)
At the start of the COVID-19 pandemic the increased market volatility and risk aversion led to a deterioration of U.S. Dollar funding conditions in the Euro Area. The swap line interventions by the ECB and Federal Reserve on March 15, 2020 aimed to alleviate the mispricing of EUR/USD FX swaps. We find that these swap line interventions were effective since they alleviated part of the mispricing. The announcement effect of the interventions is however limited; the impact of the swap line interventions is larger and more significant closer to the implementation date. This study provides insight into the effectiveness of central bank interventions in the FX swap market during turbulent periods.